2011
DOI: 10.1111/j.1863-2378.2010.01336.x
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Risk Factors forToxoplasma gondiiInfection on Finishing Swine Reared in the Umbria Region, Central Italy

Abstract: Toxoplasma gondii is a worldwide zoonotic protozoan parasite and pork is considered the major meat source of Toxoplasma infection in humans. To determine the prevalence of infection of Toxoplasma gondii in pigs reared in the Umbria Region (central Italy), blood samples of 960 pigs from 10 different farms (96 for each farm) were randomly collected and tested for antibodies (IgG) against T. gondii using an IFA assay. Sera were screened at 1/16 titrr and the endpoint titre was determined. Farm management question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
26
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 18 publications
7
26
2
1
Order By: Relevance
“…The overall prevalence of the infection was found to be 32.1%. The result of the present study was much higher than the reports from Brazil (12.5%) using indirect fluorescent antibody tests (IFAT) [35], Central Italy (16.14%) using IFAT [36], Southern Italy (16.3%) [37] using Enzyme-Linked Immunosorbent Assay (ELISA), Serbia (9.2%) [38] and Portugal (15.6%) [39] using modified agglutination test (MAT). In contrast, the present result was lower than the report from Egypt (56.6%) using MAT [40].…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…The overall prevalence of the infection was found to be 32.1%. The result of the present study was much higher than the reports from Brazil (12.5%) using indirect fluorescent antibody tests (IFAT) [35], Central Italy (16.14%) using IFAT [36], Southern Italy (16.3%) [37] using Enzyme-Linked Immunosorbent Assay (ELISA), Serbia (9.2%) [38] and Portugal (15.6%) [39] using modified agglutination test (MAT). In contrast, the present result was lower than the report from Egypt (56.6%) using MAT [40].…”
Section: Discussioncontrasting
confidence: 81%
“…Presence of cats is considered as one of the main risk factors for seropositivity in pigs, especially in animals kept in outdoor facilities. This is due to the fact that only a few oocysts are sufficient to produce infection in pigs [1,36]. Furthermore, most farm workers do not use boots and coveralls or footbaths before entering stables, thus contributing to the introduction of the oocysts collected from the environment into the pig units.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, all but one animal was positive (95.2%). If compared with the few studies carried out in confinement-raised pigs in Italy, that report seroprevalence values ranging from 16-36%; (Ranucci et al 2012;Veronesi et al 2011;Villari et al 2009), results of the present study confirm that outdoor access dramatically increases the risk for T. gondii infection.…”
Section: Accepted Manuscriptsupporting
confidence: 90%
“…T. gondii infection is widespread in pigs raised in Spain and a seroprevalence of 16.6% was obtained in a recent study (Garcia-Bocanegra et al, 2010). Similar seroprevalences were obtained in studies carried out in Italy (Villari et al, 2009;Veronesi et al, 2011), Portugal (De Sousa et al, 2006 and Germany (Damriyasa et al, 2004). Lower seroprevalence levels were found in USA (2.6%) (Hill et al, 2010), Sweden (5.2%) (Lundén et al, 2002), the Netherlands (10.9%) (Kijlstra et al, 2004) and Mexico (12.7%) (Alvarado-Esquivel et al, 2011); while higher values were observed in Serbia (28.9%) (Klun et al, 2006) and Argentina (37.8%) (Venturini et al, 2004).…”
supporting
confidence: 69%